Stem conduction systems effect on the production and quality of mini tomato under organic management - Candian, Joara Secchi [UNESP]; Menezes Martins, Bruno Novaes [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP]; Evangelista, Regina Marta [UNESP]; Fujita, Erika (Inst Agronomico, 2017)
This research evaluated the influence of stem conduction types on the production and physicochemical characteristics of tomato fruits (hybrid Coco, mini type) under organic management. The experiment was conducted between August 2013 and January 2014. The treatments consisted of 4 different conduction systems: 2 traditional stems; 2 stems emerging from axillary cotyledon buds (bottom stem); 3 traditional stems and 4 stems emerging from tip pruning. Eleven harvests were conducted from 22nd November 2013 to 31st January 2014. Data collected included fruit number per plant, yields (g.plant(-1)), fruit physicochemical characteristics, average weight, fruit diameter, pH, titratable acidity (TA), soluble solids (SS), SS/TA ratio, reducing sugars, ascorbic acid, lycopene, beta-carotene, chlorophyll-a and chlorophyll-b. Stem conduction types did not affect fruit yields per plant (g.plant(-1)). However, the greater number of stems resulted in more fruits per plant, but the fruit produced had a smaller diameter and average weight. The treatments with more stems also showed higher fruit lycopene levels, TA, and reducing sugars. Thus, under similar growing conditions, it may be recommended that organic mini tomatoes be pruned with 3 or 4 stems to increase the number of fruits per plant.
Keywords: Solanum lycopersicum L.; bottom stem; tip pruning; physicochemical characteristics